2016
DOI: 10.1371/journal.pone.0148468
|View full text |Cite
|
Sign up to set email alerts
|

Early Life Conditions and Physiological Stress following the Transition to Farming in Central/Southeast Europe: Skeletal Growth Impairment and 6000 Years of Gradual Recovery

Abstract: Early life conditions play an important role in determining adult body size. In particular, childhood malnutrition and disease can elicit growth delays and affect adult body size if severe or prolonged enough. In the earliest stages of farming, skeletal growth impairment and small adult body size are often documented relative to hunter-gatherer groups, though this pattern is regionally variable. In Central/Southeast Europe, it is unclear how early life stress, growth history, and adult body size were impacted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 133 publications
(146 reference statements)
0
28
0
Order By: Relevance
“…Important environmental influences include a combination of metabolic stress from factors such as malnutrition, poor health, and physiological stress ( 48 ) and from mechanical loading and its timing ( 49 ). There is some evidence of metabolic stress in the earliest stages of farming among these women ( 50 ) that improved through time, whereas the living women in the study were all healthy and had no history of major medical conditions, eating disorders, immobility, or medications known to affect bone. If dietary and health status affected the cortical thickness or endosteal contour of prehistoric women, then that would be undetectable using solid-section CSG properties derived solely from the periosteal contour and could be contributing slightly to the magnitude of differences between prehistoric and living women.…”
Section: Discussionmentioning
confidence: 93%
“…Important environmental influences include a combination of metabolic stress from factors such as malnutrition, poor health, and physiological stress ( 48 ) and from mechanical loading and its timing ( 49 ). There is some evidence of metabolic stress in the earliest stages of farming among these women ( 50 ) that improved through time, whereas the living women in the study were all healthy and had no history of major medical conditions, eating disorders, immobility, or medications known to affect bone. If dietary and health status affected the cortical thickness or endosteal contour of prehistoric women, then that would be undetectable using solid-section CSG properties derived solely from the periosteal contour and could be contributing slightly to the magnitude of differences between prehistoric and living women.…”
Section: Discussionmentioning
confidence: 93%
“…However, many studies have shown that male offspring are more susceptible to malnutrition in early life (279), most likely because their faster growth rate makes them more sensitive to any constraints on energy supply. Of interest here, there is evidence for more significant body size shifts among men than women (220), which suggests that male offspring disproportionately picked up the signal of energetic stresses affecting adult women.…”
Section: The Central Role Of Women and Inter-generational Effectsmentioning
confidence: 84%
“…As the effect of this data is moderated in the models presented here, it appears questionable if the negative impact of Secondary Neolithization in Southeastern Europe on stature at ca. 6000 BC was indeed as sharp as signaled by unmodeled data (e.g., Macintosh et al 2016;Rosenstock and Scheibner 2018). Rather, some stature decrease already starts around ca.…”
Section: Stature Variation In the Context Of Current Anthropometric mentioning
confidence: 85%
“…Hence, long bone lengths or body heights estimated from them-a procedure for which a variety of formulas is available (for overviews, see, e.g., Rösing 1988;Moore and Ross 2013;Zeman et al 2014)-are the only universally available proxies for stature. Several studies have so far used long bone lengths or stature estimations to address early body height development for various regions, especially in Old World Archaeology (e.g., Angel 1984;Bennike 1985;Jaeger et al 1998;Koca Özer et al 2011;Siegmund 2010;Piontek and Vančata 2012;MacIntosh et al 2016). One first broader study on Central, Western, and Northern Europe has only appeared very recently , but leaves aside Southeastern Europe, the Mediterranean, and the Near East, which are key areas for many prehistoric socioeconomic developments.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation